Protocol for a scoping review of patient–clinician digital health interventions for the population with hip fracture. Issue 11 (23rd November 2022) - Backman, Chantal; Papp, Steve; Harley, Anne; Houle, Sandra; Skidmore, Becky; Poitras, Stephane; Green, Maeghn; Shah, Soha; Berdusco, Randa; Beaulé, Paul; French-Merkley, Véronique
Abstract : Introduction: Patient–clinician digital health interventions can potentially improve the care of patients with hip fracture transitioning from hospital to rehabilitation to home. Assisting older patients with a hip fracture and their caregivers in managing their postsurgery care is crucial for ensuring the best rehabilitation outcomes. With the increased availability and wide uptake of mobile devices, the use of digital health to better assist patients in their care has become more common. Among the older adult population, hip fractures are a common occurrence and integrated postsurgery care is key for optimal recovery. The overall aims are to examine the available literature on the impact of hip fracture-specific patient–clinician digital health interventions on patient outcomes and healthcare delivery processes; to identify the barriers and enablers to the uptake and implementation of these digital health interventions; and to provide strategies for improved use of digital health technologies. Methods and analysis: We will conduct a scoping review using Arksey and O'Malley's methodology framework and following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Statement for the Scoping Reviews reporting format. A search strategy will be developed, and key databases will be searched until approximately May 2022. A two-step screening process and data extraction of included studies will be performed by two reviewers. Any disagreement will be resolved by consensus or by a third reviewer. For the included studies, a narrative data synthesis will be conducted. Barriers and enablers identified will be mapped to the domains of the Theoretical Domains Framework and related strategies will be provided to guide the uptake of future patient–clinician digital health interventions. Ethics and dissemination: This review does not require ethics approval. The results will be presented at a scientific conference and published in a peer-reviewed journal. We will also involve relevant stakeholders to determine appropriate approaches for dissemination.